Analysis of Factors Influencing Wait Times at Disneyland Resort - Wei, He (International Journal of Computer Science and Information Technology, 2024)
This paper aims to enhance the accuracy of wait time predictions and optimize park management at Disneyland, a popular leisure destination facing long wait times for attractions. These wait times adversely affect visitors' immediate experiences and overall evaluations, influencing their willingness to return. These wait times adversely affect visitors' immediate experiences and overall evaluations, influencing their willingness to return. The study employs advanced data analysis and machine learning algorithms to develop high-precision wait time prediction models. Utilizing big data techniques, the research integrates multi-dimensional data, including weather, visitor flow, and historical wait times, to optimize resource allocation and improve operational efficiency. optimize resource allocation and improve operational efficiency and visitor satisfaction. The study further explores the application of these models in other domains such as healthcare, healthcare, and healthcare services. The study further explores the application of these models in other domains such as healthcare and transportation, demonstrating the potential for cross-disciplinary technology transfer to enhance overall service quality and efficiency. The findings underscore the significant impact of big data behavior analysis in theme park management, contributing to the findings underscore the significant impact of big data behavior analysis in theme park management, contributing to increased visitor satisfaction, enhanced competitiveness, and long-term sustainability of the park.